POLA KOMUNIKASI ANTARPRIBADI PELATIH DAN ATLET CABANG OLAHRAGA LAYAR PROVINSI JAWA BARAT(Studi Kasus Meningkatkan Prestasi dalam Persiapan Menghadapi PON 2021) - Fitri Alwiyah (2021)
Interpersonal communication between coaches and athletes is two-way communication which is carried out directly through face to face in training activities and outside training. The problem that often arises in the relationship between coaches and athletes is the lack of good communication between the coach and the athletes, such as athletes misinterpreting messages or not understanding what is explained by the coach and the openness between them. Therefore, the coach needs to adjust the way of communicating with the athletes and pay attention to the characteristics of each athlete and give equal attention without discrimination which is supported by the communication competence of the coach. This study aims to determine the interpersonal communication patterns of coaches and athletes in the West Java Province Sail sport as well as inhibiting and supporting factors. The method used in this research is a qualitative method with a case study approach obtained through interviews with several informants who have been determined. The theory used in this research is competency theory. The results of the research carried out were the form of communication carried out by the coach and the sailor athletes through the process of sending and receiving messages that were carried out during training or competing directly through various communication activities, this was inseparable from creating good communication between the coach and the Sail athletes. So that the message conveyed is not only through verbal communication but also uses nonverbal communication through movements, symbols or supporting tools in interacting so that the communication carried out is easy to understand as a whole in an appropriate way so that it can form a closeness that is honest, open and trusting between coaches and athletes who walk according to a common goal. The inhibiting factor is the loss of focus in training, then there is a high sense of ego in the athlete and the fear, awkwardness and prestige that exist in the athlete's self-problems and supporting factors, namely openness, cooperation, discipline.